Uncertainty, financial crises, and subjective well-being - Lena Tonzer (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2017)
This paper focuses on the effect of uncertainty as reflected by financial market variables on subjective well-being. The analysis is based on Eurobarometer surveys, covering 20 countries over the period from 2000 to 2013. Individuals report lower levels of life satisfaction in times of higher uncertainty approximated by stock market volatility. This effect is heterogeneous across respondents: The probability of being unsatisfied is higher for respondents who are older, less educated, and live in one of the GIIPS countries of the euro area. Furthermore, higher uncertainty in combination with a financial crisis increases the probability of reporting low values of life satisfaction.
urn:nbn:de:gbv:3:2-67709
Keywords: D60; G01; I31; 330; subjective well-being; uncertainty; financial crises